2012
DOI: 10.1080/09603123.2010.484860
|View full text |Cite
|
Sign up to set email alerts
|

Association between early methylmercury exposure and functional health among residents of the Shiranui Sea communities in Japan

Abstract: The objective of this study was to evaluate the effect of estimated historical methylmercury exposure on the functional health of residents living in the Shiranui Sea communities in Japan. Functional health was measured by self-reported activities of daily living (ADL). Study areas were categorized into high, medium and low methylmercury exposure areas according to their location or distance from the Shiranui Sea. We estimated the adjusted prevalence odds ratios of impaired ADL in relation to exposure using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Hair-Hg concentrations of fish consumers during the `Minamata disease` outbreak ranged from 191 μg/g to 705μg/g (Koos and Longo, 1976;Harada, 1982). A recent study in Japan showed that residents who were exposed to elevated MeHg historically still showed significant functional deficit decades later (Ushijima et al 2012).…”
Section: Effects On Fish Consuming Adultsmentioning
confidence: 99%
“…Hair-Hg concentrations of fish consumers during the `Minamata disease` outbreak ranged from 191 μg/g to 705μg/g (Koos and Longo, 1976;Harada, 1982). A recent study in Japan showed that residents who were exposed to elevated MeHg historically still showed significant functional deficit decades later (Ushijima et al 2012).…”
Section: Effects On Fish Consuming Adultsmentioning
confidence: 99%